2018
DOI: 10.2991/j.jegh.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The Predictive Value of Personality Traits for Psychological Problems (Stress, Anxiety and Depression): Results from a Large Population Based Study

Abstract: The current study aimed to determine the prognostic values of personality traits for common psychological problems in a large sample of Iranian adult. In a large sample of healthy people (n = 4763) who lived in Isfahan province; the NEO-FFI was used to assess the personality traits; depression and anxiety were assessed using the "Hospital Anxiety and Depression Scale (HADS)" also stress was measured through Persian validated version of General Health Questionnaire (GHQ-12). Receiver Operating Characteristics C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 63 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…Neuroticism is also believed to be a reliable predictor of reduced life satisfaction [73]. An Iranian study into the predictive value of personality in diagnosing stress, anxiety, and depression found that neuroticism was the only significant predictor of all three mental health problems [74]. Similarly, a Finnish study that sought to ascertain university student interest in using a stress management app reported that extraversion, agreeableness, and conscientiousness were associated with lower self-reported stress whereas neuroticism was strongly associated with rumination, anxiety, and depression [75].…”
Section: Personality and Stressmentioning
confidence: 99%
“…Neuroticism is also believed to be a reliable predictor of reduced life satisfaction [73]. An Iranian study into the predictive value of personality in diagnosing stress, anxiety, and depression found that neuroticism was the only significant predictor of all three mental health problems [74]. Similarly, a Finnish study that sought to ascertain university student interest in using a stress management app reported that extraversion, agreeableness, and conscientiousness were associated with lower self-reported stress whereas neuroticism was strongly associated with rumination, anxiety, and depression [75].…”
Section: Personality and Stressmentioning
confidence: 99%
“…The HADS tool has been proven to demonstrate a sensitivity of >80% and specificity of >90% in the Chinese elderly [20]. Subjects with scores for either sub-scale for anxiety or depression of >7 were defined as having possible depression or anxiety; otherwise, the subject was considered normal mental status [21,22].…”
Section: Mental Health Assessmentmentioning
confidence: 99%
“…Individuals with emotional stability tend to be calm in facing problems, have self-confidence and firm principles. However, the negative characteristics of neuroticism are being easily nervous, depressed, not confident and easily changing their mind 5 A study proved that there is an influence between stress and the occurrence of hypertension in pregnant women 10 . This is because they are unable to overcome the problems faced by their mental, physical and emotional health.…”
Section: Personality and Locus Of Controlmentioning
confidence: 99%